I have this question:

The polynomial $f(x) = x^6 - ax^4 - ax^2 +1 $ has $(x-p)$ as a factor, where $a,p$ are real numbers. Show that $a = p^2 + p^{-2} - 1$

Here's my attempt:

Let $u = x^2 \implies f(x) = u^3 - au^2 - au + 1$

Let $\alpha, \beta, \gamma$ be the roots of this polynomial.

Since $(x-p)$ is a factor of the original polynomial, it follows that $\alpha = p^2$.


$\alpha + \beta + \gamma = a \implies \beta + \gamma = a - p^2$

$\alpha \beta \gamma = -1 \implies \beta \gamma = -\frac{1}{p^2}$

$\alpha \beta + \beta \gamma + \gamma \alpha = -a$

$\therefore p^2(\beta + \gamma) + \beta \gamma = -a$

$p^2(a-p^2) - \frac{1}{p^2} = -a$

I then continued in this vein for some time, trying to rearrange the expression to prove the result shown in the question. I couldn't do it. Am I going about this the right way, or am I completely wrong? If I'm right, where do I go from here?


The polynomial $f(x) = x^6 - ax^4 - ax^2 +1 $ has $(x-p)$ as a factor iff $f(p)=0$.

Now $0=f(p)=p^6 - ap^4 - ap^2 +1$ and so $a(p^4+p^2)=p^6+1=(p^2+1) (p^4-p^2+1)$, because $u^3+1=(u+1)(u^2-u+1)$.

Cancelling $p^2+1$, which is never zero, we get $ap^2 = p^4-p^2+1$, which is equivalent to $a = p^2 + p^{-2} - 1$ because $p\ne 0$.






Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.